Mono-, di- and tetra-nuclear p-cymeneruthenium complexes containing oxalato ligands - Yan, Hong; Süss-Fink, Georg; Neels, Antonia; Stoeckli-Evans, Helen (My University, 1997)
The oxalato complexes [Ru2(µ-η4-C2O4)Cl2(η6-p-PriC6H4Me)2] 1 and [Ru(η2-C2O4)(NH3)(η6-p-PriC6H4Me)] 2 have been prepared from the reaction of ammonium oxalate with [{RuCl2(η6-p-PriC6H4Me)}2] and [Ru(H2O)3(η6-p-PriC6H4Me)]2+, respectively. With triphenylphosphine, 1 reacted to give [Ru2 (µ-η4-C2O4)(PPh3)2 (η6-p-PriC6H4Me)2]2+3, while 2 gave [Ru(η2-C2O4)(PPh3)(η6-p-PriC6H4Me)] 4. The dichloro complex 1 can also be converted into the cationic dimethanol complex [Ru2 (µ-η4-C2O4)(MeOH)2(η6-p-PriC6H4Me)2]2+5 by precipitation of the chloride with a silver salt in methanol. Complex 5 reacted with 4,4-bipyridine to afford a novel tetranuclear metallomacrocycle [Ru4(µ-η4-C2O4)2(µ-η1:η1-bipy)2 (η6-p-PriC6H4Me)4]4+6 with alternating oxalato and 4,4-bipyridine bridges. The reaction between 1 and azide yielded the known azido-bridged complex [{Ru(µ-η1-N3)Cl(η6-p-PriC6H4Me)}2] 7. The molecular structures of 1 (two conformational isomers), 4, 5 and 6 have been solved by X-ray crystallography.